Cyanobacteria blooms: from impacts on the environment to management strategies - Cong, Danni (Kansas State University, 2015)
Bloom-forming cyanobacteria are harmful to both environment and public health because of the release of water soluble toxins. This report provides a broad overview of cyanobacteria and cyanotoxins and the current state of knowledge about the bloom control management. Cyanobacteria blooms usually flourish in warm, lentic, and eutrophic waters. Several environmental factors such as temperature, nutrients, light intensity, and turbulence can affect cyanobacterial growth and the formation of bloom. Cyanobacteria can synthesize multiple types of toxins, which cause human and animal toxications worldwide. Cyanobacterial blooms also cause detrimental effects on aquatic ecosystems, and the taste and odor problems in drinking water supplies. Due to the adverse effects, treatments that are used for removing both cyanobacterial cells and aqueous cyanotoxins should be carried out once cyanobacterial blooms occur in freshwaters. Strategies based on physical, chemical, and biological methods are carried out to remove the cyanobacteria and cyanotoxins. All of these strategies have both advantages and disadvantages: some physical treatment methods can remove cyanotoxins within the intact molecules, but the cost is usually high and further processing is needed; some chemical methods are cheap and can degrade the cyanotoxins, however, the toxicological characterization of the chemical and the by-products needs to be investigated; some biological treatments are more environmentally friendly, but the long reaction time and some other external factors also pose some problems that affect the efficiency of the treatments. The paper concludes that the key to success is to find a reasonable balance between those advantages and disadvantages, and the specific conditions of each unique aquatic ecosystem should be taken into consideration. As well, some suggestions are also proposed for the further development of more robust monitoring and management strategies.
Keywords: Cyanobacteria Blooms Management; Environmental Engineering (0775)